Psychiatrists’ attitudes and knowledge towards treating asylum seeker and refugee subjects in the UK - Tham, Dominique; Yeskendir, Alua; Grant-Peterkin, Hugh; Hameed, Yasir; Pillay, Mishka; Kirkbride, James B. (BJPsych open, 2025)
Over 1% of the world's population have been forcibly displaced. Asylum seekers and refugees (ASR) are at higher risk of serious mental illnesses. Despite a high need for care, little is known about the attitudes, knowledge and competencies of psychiatrists who may treat ASR subjects. The study aimed to identify perceived gaps in psychiatric training that could help guide medical education and policymaking related to treating ASR mental health. We conducted the first national survey of UK-based psychiatrists to assess attitudes, knowledge and competencies around treating ASR subjects. The online survey was sent to all psychiatrists ( = 18 182) and registered trainees ( = 4700) on the Royal College of Psychiatrists databases in 2022. We used exploratory and confirmatory factor analyses to identify the optimal factor structure underlying the questionnaire. Variations in scores on extracted latent constructs by sociodemographic and clinical variables were explored using linear regression. Data from 609 psychiatrists (77%) and trainees (22%) were included in the final analysis. We identified four latent constructs concerning perceived knowledge, positive attitudes, negative attitudes and perceived distress. Only 42% of respondents felt they had sufficient knowledge to work competently with ASR subjects, and 34.7% found the work emotionally distressing. Greater knowledge predicted both more positive ( = 0.26, 95% CI: 0.20-0.33) and more negative ( = 0.17, 95% CI: 0.09-0.26) attitudes, and was associated with less self-reported distress among psychiatrists ( = -0.34, 95% CI: -0.43 to -0.21). Female psychiatrists reported more distress related to treating ASR subjects ( = 0.29, 95% CI: 0.14-0.44). Less than half of psychiatrists in this survey believed they possessed adequate knowledge to treat ASR subjects, and some found working with such individuals distressing. Our results suggest that these issues could be mitigated by improving knowledge related to treating ASR subjects.